Budaya Perundungan Dan Isu Sosial Dalam Serial Drama Pyramid Game - Nur Chasanah, Ajilni Diini Mar'atun (Maliki Interdisciplinary Journal, 2025)
This research focuses on bullying, social issues, and the conflicts that cause it to occur. Bullying is an aggressive act aimed at hurting and controlling individuals who are perceived as weaker and having lower power. This study employs a qualitative method, with data collection techniques including observation and note-taking, and data analysis using Miles & Huberman’s theory, which consists of data reduction, data presentation, and data validation. The findings of this research reveal several sources of conflict, including: Individual differences, Cultural differences, Differences in interests, and Social change. From these results, it can be concluded that bullying has a significant impact on the mental health and physical well-being of its victims.